Determining PID Parameters For Temperature Control System in Cavendish Banana Storage Room : Menentukan Parameter PID Untuk Sistem Kendali Suhu Pada Ruang Penyimpanan Pisang Cavendish - Arifuddin, Rahman; Subairi, Subairi; Setiawan, Aries Boedi; Ridlo, Muhammad Ali; Ziliwu, Alsaro Natanael (Muhammadiyah University, Sidoarjo, 2024)
Banana is one of the most popular fruits in Indonesia, and its freshness will be the top priority for consumers in choosing it. After packaging, special treatment needs to be done in the banana storage room. One of them is to keep the temperature of the storage room stable. The temperature of the room between 5oC to 10oC is the ideal temperature for storing bananas, the Control system offered is PID with the Ziegler-Nichols method to get the values of Kp, Ki and Kd. Determination of Kp, Ki and Kd values is very important to get good system stability and a small error. The tuning rule of Ziegler-Nichols 1 method can be applied to obtain the values of Kp, Ki and Kd. With several steps taken, the values of L = 90s and T = 206s are obtained and referring to the Ziegler-Nichols 1 table, the values of Kp = 2.7, Ki = 0.015 and Kd = 121.5 are determined.